From rough mereology to robust navigation: Expanding mobile robot strategies with diverse maps and enhanced goal-targeting mechanisms - Szpakowska, Aleksandra; Artiemjew, Piotr; Cybowski, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
Path planning is one of the most important problems in mobile robotics. Particularly challenging in selecting an appropriate path planning method is the choice of a method for complex obstacle configurations. The problems of path planning, among many other methods, come into play with approaches based on the application of potential fields methodology based on physical anomalies with gravitational or electromagnetic fields. This idea makes it possible to navigate in complex maps.
Keywords: rough mereology; mobile robotics; path planning